NUTRITIONAL SCREENING OF ELDERLY BY DIFFERENT METHODS AND INDICATORS ADMITTED TO HOSPITAL - de Oliveira, Fernanda Cristina Esteves; de São José, Jackline Freitas Brilhante; Paula, Hudsara Aparecida de Almeida; Ribeiro, Andréia Queiroz; Gomide, Carla Iamin; Alfenas, Rita de Cássia Gonçalves (DEMETRA: Alimentação, Nutrição & Saúde, 2016)
Objective: Identify appropriate methods and indicators to assess elderly nutritional status admitted to a hospital. Methods: Cross-sectional study in which 41 elderly patients of both sexes were evaluated (≥ 60 years). Body weight, height, body mass index (BMI), brachial circumference (BC), waist circumference (WC), calf circumference (CC), hematocrit, hemoglobin, and total lymphocyte count were evaluated. The Mini Nutritional Assessment (MNA) was also applied. Results: Among 41 elderly evaluated, 53.7% were female. The classification of the nutritional status obtained through MNA and BMI showed that 80.48% and 70.73% of the elderly were diagnosed with inadequate nutritional status, respectively. Strong positive correlation between MNA x BMI, MNA x CC, MNA x BC, BMI x CC and BMI x BC was observed. Kappa analysis showed a moderate agreement only between MNA x BMI and MNA e BC. Conclusion: The results suggest that MNA, BMI and BC were the most suitable methods for nutritional screening of hospitalized elderly. DOI: 10.12957/demetra.2016.18071